2011
DOI: 10.1159/000327891
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pulmonary Artery Hypertension in Preterm Infants with Moderate or Severe Bronchopulmonary Dysplasia

Abstract: Background: Despite the potential importance of pulmonary artery hypertension (PAH) in preterm infants with bronchopulmonary dysplasia (BPD), little is known about the risk factors for PAH. Objectives: To investigate the risk factors for PAH in preterm infants with BPD. Methods: Infants diagnosed with BPD were assigned to the PAH group or non-PAH group except for infants with mild BPD who had no PAH. PAH was diagnosed on the basis of echocardiograms demonstrating elevated right ventricle pressure beyond the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
141
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 55 publications
5
141
5
Order By: Relevance
“…A recent study by Mirza and coworkers described a lower incidence of PH (8% at 10-14 d of age and 4% at 36 wk PMA), but the criteria for PH diagnosis in that study was more similar to our alternate criteria-1 (41), which achieved similar rates of PH in our cohort (Figure 2). Higher death rates in preterm infants with BPD and PH compared with those without PH have been reported as well (24,40,42). Factors associated with late PH in these studies include lower birthweight and longer periods of respiratory support.…”
Section: Discussionmentioning
confidence: 82%
“…A recent study by Mirza and coworkers described a lower incidence of PH (8% at 10-14 d of age and 4% at 36 wk PMA), but the criteria for PH diagnosis in that study was more similar to our alternate criteria-1 (41), which achieved similar rates of PH in our cohort (Figure 2). Higher death rates in preterm infants with BPD and PH compared with those without PH have been reported as well (24,40,42). Factors associated with late PH in these studies include lower birthweight and longer periods of respiratory support.…”
Section: Discussionmentioning
confidence: 82%
“…Bronchopulmonary dysplasia (BPD) is associated with pulmonary hypertension (PH), [1][2][3] with BPD-PH occurring in 30% to 45% of infants with moderate to severe BPD. 1,3,4 Mortality rates in infants with BPD-PH are 4-fold greater than in infants without PH, with the majority of deaths linked directly to PH.…”
mentioning
confidence: 99%
“…1,3,4 Mortality rates in infants with BPD-PH are 4-fold greater than in infants without PH, with the majority of deaths linked directly to PH. 3,5 Supplemental oxygen is the mainstay of therapy for patients with BPD-PH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PAH is common in infants with BPD, with an estimated incidence of 18%-25% of preterm infants, [79][80][81] and is associated with high mortality (30%-40%), especially if sustained beyond the first months of life. [82][83][84][85] Although long-term studies of BPD have primarily focused on late abnormalities of airway function, PVD can also persist into childhood and adult life. 79,[86][87][88][89] Tepper and colleagues 88 have reported that infants with even mild BPD have decreased diffusion capacity when corrected for lung volume, in comparison with age-matched term controls, suggesting that BPD infants may have decreased alveolar surface area available for gas exchange.…”
Section: Pvd In Bpdmentioning
confidence: 99%